Survey of ear anthropometry for young college students in China and its implications for ear‐related product design. Issue 1 (28th September 2020) - Lu, Peixian; Tsao, Liuxing; Yu, Chen; Ma, Liang
Abstract: Ear anthropometry plays an important role in ear‐related product design. However, current Chinese ear anthropometry data do not provide sufficient guidance for product designers targeting young Chinese consumers. In this study, an ear anthropometry survey of 1338 young Chinese college students was conducted using photogrammetry. Eight key dimensions were determined, measured, and statistically analyzed: ear height, ear width, ear length, cavum conchae height, cavum conchae width, ear connection height, ear lobe height, and ear lobe width. Interethnic, intergender, subject‐specific, and intrasubject differences were explored and discussed, based on the collected data. In addition, ear shape classification was conducted using principal component analysis to recommend an ear‐related product sizing system. The data obtained in this survey can be used as a reference for ear‐related product design targeting young Chinese consumers.